Isl1 Controls Patterning and Mineralization of Enamel in the Continuously Renewing Mouse Incisor - Naveau, Adrien; Zhang, Bin; Meng, Bo; Sutherland, McGarrett T; Prochazkova, Michaela; Wen, Timothy; Marangoni, Pauline; Jones, Kyle B; Cox, Timothy C; Ganss, Bernhard; Jheon, Andrew H; Klein, Ophir D (Journal of bone and mineral research, 2017)
Rodents are characterized by continuously renewing incisors whose growth is fueled by epithelial and mesenchymal stem cells housed in the proximal compartments of the tooth. The epithelial stem cells reside in structures known as the labial (toward the lip) and lingual (toward the tongue) cervical loops (laCL and liCL, respectively). An important feature of the rodent incisor is that enamel, the outer, highly mineralized layer, is asymmetrically distributed, because it is normally generated by the laCL but not the liCL. Here, we show that epithelial-specific deletion of the transcription factor Islet1 (Isl1) is sufficient to drive formation of ectopic enamel by the liCL stem cells, and also that it leads to production of altered enamel on the labial surface. Molecular analyses of developing and adult incisors revealed that epithelial deletion of Isl1 affected multiple, major pathways: Bmp (bone morphogenetic protein), Hh (hedgehog), Fgf (fibroblast growth factor), and Notch signaling were upregulated and associated with liCL-generated ectopic enamel; on the labial side, upregulation of Bmp and Fgf signaling, and downregulation of Shh were associated with premature enamel formation. Transcriptome profiling studies identified a suite of differentially regulated genes in developing Isl1 mutant incisors. Our studies demonstrate that ISL1 plays a central role in proper patterning of stem cell-derived enamel in the incisor and indicate that this factor is an important upstream regulator of signaling pathways during tooth development and renewal. © 2017 American Society for Bone and Mineral Research.
Keywords: proteiny s homeodoménou LIM; Signal Transduction; zubní sklovina; rozvržení tělního plánu; Transcription Factors; Mutation; LIM-Homeodomain Proteins; Body Patterning; Calcification, Physiologic; transkripční faktory; Mice; zvířata; Gene Expression Regulation, Developmental; sekvenční analýza RNA; epitel; signální transdukce; Mandible; delece genu; Epithelium; mandibula; řezáky; vývojová regulace genové exprese; Organ Specificity; Sequence Analysis, RNA; Gene Deletion; myši; ženské pohlaví; stanovení celkové genové exprese; orgánová specificita; Animals; fyziologická kalcifikace; Gene Expression Profiling; mutace; Incisor; Dental Enamel; Female